ȘAPTE CORELAȚII ÎNTRE VIOLENȚA INTERPERSONALĂ ȘI PROGRESUL RELIGIEI ORGANIZATE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Seven correlations between interpersonal violence and the progression of organised religion.While the majority of organised religions determine the origins of religion itself in an act of divine revelation, social science literature takes an evolutionary perspective. Without engaging the question of origin of religion from either perspective, this article proposes seven correlations between interpersonal violence and the progression of organised religion by suggesting that interpersonal violence plays a significant role in the institutionalising process of organised religion. Although interpersonal violence does not necessarily cause the structuring of faith, it reinforces and provides solutions to the existing patterns of threat faced by the community, which together lead to the organisation of religion. The first part of this article (stages 1–4) surveys the psychology of violence by focusing on the theories of frustration–aggression, mimetic rivalry, triangulation and the genesis of scapegoating and guilt. The second part (stages 5–6) marks the transition from personal to social psychology and surveys violence in the primitive religion, as manifested in the ritualising process of the scapegoat, and the genesis of sacrifice. The third part (stage 7) highlights the complexity of ritual, ethics and doctrine, in the evolution of religion from a primitive state to an advanced organised institution.